2020
DOI: 10.1007/s13300-020-00869-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Characteristics of Gastrointestinal Adverse Events with Once-Weekly Dulaglutide Treatment in Chinese Patients with Type 2 Diabetes: A Post Hoc Pooled Analysis of Two Randomized Trials

Abstract: Introduction Gastrointestinal (GI) events are a common side effect of glucagon-like peptide 1 (GLP-1) receptor agonists (RA) class. This post hoc analysis assessed the characteristics of GI adverse events in Chinese patients with type 2 diabetes (T2D) who were treated with once-weekly dulaglutide from two randomized clinical trials. Methods Chinese patients with T2D, treated with once-weekly dulaglutide (1.5 mg and 0.75 mg) from two phase III multicenter trials (AWARD-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(97 reference statements)
2
1
0
Order By: Relevance
“…Concerning adverse events, GI events are common side effects of GLP1 RAs. In our study, 37.14% of the PCOS participants with dulaglutide treatment reported at least one GI TEAE, which was comparable with those observed in individuals with T2D receiving 1.5 mg once-weekly dulaglutide as described in the Assessment of Weekly AdministRation of LY2189265 in Diabetes (AWARD) trials [ 46 , 47 ]. Compared with the AWARD studies [ 46 , 47 ], the current study had higher incidences of nausea, vomiting, constipation, and loss of appetite.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Concerning adverse events, GI events are common side effects of GLP1 RAs. In our study, 37.14% of the PCOS participants with dulaglutide treatment reported at least one GI TEAE, which was comparable with those observed in individuals with T2D receiving 1.5 mg once-weekly dulaglutide as described in the Assessment of Weekly AdministRation of LY2189265 in Diabetes (AWARD) trials [ 46 , 47 ]. Compared with the AWARD studies [ 46 , 47 ], the current study had higher incidences of nausea, vomiting, constipation, and loss of appetite.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, 37.14% of the PCOS participants with dulaglutide treatment reported at least one GI TEAE, which was comparable with those observed in individuals with T2D receiving 1.5 mg once-weekly dulaglutide as described in the Assessment of Weekly AdministRation of LY2189265 in Diabetes (AWARD) trials [ 46 , 47 ]. Compared with the AWARD studies [ 46 , 47 ], the current study had higher incidences of nausea, vomiting, constipation, and loss of appetite. A possible explanation for this might be the younger study population, and more GI events might have occurred in the higher baseline BMI subgroups [ 48 ].…”
Section: Discussionsupporting
confidence: 77%
“…Bettge and colleagues reported that only a small percentage (\15%) of patients in their study discontinued dulaglutide treatment in the first year of treatment [30]. According to a very recent observation on Chinese patients with T2D (N = 787) who were treated with dulaglutide once weekly in two phase III multicenter trials (AWARD-CHN1 and AWARD-CHN2) [31], most of the gastrointestinal AEs associated with dulaglutide were mild to moderate in severity; their incidence was more pronounced during the first 2 weeks of dulaglutide treatment but declined rapidly as treatment continued. Healthcare providers should take gastrointestinal-related issues into account when prescribing a GLP-1RA, but disparities between patient experiences and physician perceptions have been revealed, suggesting gaps in physician-patient communication [32].…”
Section: Discussionmentioning
confidence: 99%